(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes issues such as the management process and the formation of the leader as a speaker, the history of the study of management as a theoretical science, the art of management, the influence of management, management psychology, social psychology, and the leader’s social role in management.